2021
DOI: 10.1371/journal.pntd.0009570
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi-infected Rhodnius prolixus endure increased predation facilitating parasite transmission to mammal hosts

Abstract: Triatomine bugs aggregate with conspecifics inside shelters during daylight hours. At dusk, they leave their refuges searching for hosts on which to blood feed. After finding a host, triatomines face the threat of being killed, because hosts often prey on them. As it is known that many parasites induce the predation of intermediate hosts to promote transmission, and that ingestion of Trypanosoma cruzi-infected bugs represents a very effective means for mammal infection, we hypothesized that trypanosomes induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
1
6
1
Order By: Relevance
“…The incongruences observed between our results and other reports, which are focused on the feeding and defecation behavior, could be associated, among others, with the different vector and parasite ( T. cruzi / T. rangeli ) combinations or genotypes, their parasite load, their starvation time, time after infection, or different pre-experimental and experimental blood sources [ 15 , 16 , 17 , 18 , 19 , 26 , 50 ]. Although these differences make direct comparisons difficult, all of these investigations confirm that T. cruzi modifies the behavior of their hosts.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The incongruences observed between our results and other reports, which are focused on the feeding and defecation behavior, could be associated, among others, with the different vector and parasite ( T. cruzi / T. rangeli ) combinations or genotypes, their parasite load, their starvation time, time after infection, or different pre-experimental and experimental blood sources [ 15 , 16 , 17 , 18 , 19 , 26 , 50 ]. Although these differences make direct comparisons difficult, all of these investigations confirm that T. cruzi modifies the behavior of their hosts.…”
Section: Discussioncontrasting
confidence: 99%
“…Verly et al (2020) [ 59 ], observed that Triatoma rubrovaria (Blanchard, 1843) infected with T. cruzi ingested about 25% more blood than non-infected insects. Our results and others [ 17 ] show that there seems to be a taxon-specific effect of the infection, as infected T. infestans show the same tendency to increase the number of bites, but also to ingest and retain more blood, unlike other triatomine species. The amount of blood ingested seems to be positively influenced by the T. cruzi infection [ 59 ].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The decision to leave a shelter and engage in foraging is risky, as triatomine hosts are often predators as well. For this reason, starved bugs mostly leave the protection of the shelters when a robust set of host clues is present [3][4][5]. Bugs of all nymphal instars and adults of both sexes feed on blood and can tolerate long starvation.…”
Section: Introductionmentioning
confidence: 99%